The Effect Of Service Quality On The Behavioral Loyalty Of Consumers In After-Sales Services (A Case Study On Toyota Car Users In Syria) - زين العابدين, دانيا; ماخوس , ديمة; زيدان, محمد (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The aim of the research was to study the effect of after-sales service quality dimensions on the behavioral loyalty of Toyota car users in Syria, whose market is characterized by details and variables that are not available in other markets. The researcher chose a random sample of the study population of (421) clients, to whom a questionnaire was distributed, (401) questionnaires were retrieved, and (10) questionnaires were excluded for not completing their data, thus the number of questionnaires that were unloaded was (391). The researcher analyzed the data using the statistical analysis program (SPSS 20). The study adopted the descriptive analytical approach. The results of the research indicated that the tangibility of the service had a strong significant effect on the behavioral loyalty of customers, while it was interesting that the empathy dimension had no significant and important effect in achieving And improving the behavioral loyalty of customers. Therefore, the maintenance agent must focus on the dimensions of tangibility, reliability and responsiveness to achieve high levels of customer loyalty and retention, thus maintaining the market share of the organization and increasing its profits.